Analisis Marketing Mix 4P Terhadap Tingkat Kepuasan Pasien Rawat Jalan Poli Bedah Umum Rumah Sakit Umum Daerah Dr. Mohamad Soewandhie - Vincent Aurelius Gonaldy; Minarni Wartiningsih; Billy Daniel Messakh (Ranah Research : Journal of Multidisciplinary Research and Development, 2023)
Outpatient satisfaction level takes an important role in hospital success. Outpatient satisfaction levels are determined by various factors, some of them are mentioned in the Marketing Mix 4p strategy that includes place, promotion, price, product. Marketing mix (place) includes strategic location, comfortability and cleanliness of public toilet, comfortability and cleanliness of consultation room, comfortability and cleanliness of waiting room and parking space availability. Marketing mix (promotion) includes any action that the company or hospital had taken to persuade patients to use the hospital services. Marketing mix (price) includes service cost, easy access to conduct transaction, suitability of prices compared to services received, medicine price and thorough explanation for proof of payment. Marketing mix (product) includes informed consent from healthcare workers, services received from nurses, services received from pharmacists, consultation services and availability of medicines. A study was needed to determine the relation between marketing mix strategy and level of outpatient satisfaction the purpose of this study was to determine if marketing mix 4p is related to outpatient satisfaction. This study is a quantitative study with Cross Sectional design and observational analytics design. The methods that were used to analyze in this study is statistical analysis. The data used in this study was primary taken by asking outpatient to fill in questionnaires. The study’s sample were 106 people who were chosen using the systematic random sampling technique. The study was conducted at the general surgery clinic at dr. Mohamad Soewandhie regional hospital starting from 20th of September 2023 to 31st October 2023. In this study, marketing mix 4p strategy was divided into 4 variables (place, promotion, price, product). Spearman Correlation tests for marketing mix (place) were made and resulting in a value of p = 0.337 (p > 0.05) and coefficient correlation r = 0.094. Spearman Correlation tests for marketing mix (promotion) were made, and result in a value of p = 0.358 (p > 0.05) and coefficient correlation r = 0.090. Spearman Correlation tests for marketing mix (price) were made, and a result of p value = 0.935 (p > and coefficient correlation r = - 0.008. Spearman Correlation tests were made, and a result in a value of p = 0.44 (p < 0.05) and coefficient correlation r = 0.764. Based on the results that were found it can be concluded that there was a significant association between marketing mix (product) and outpatient satisfaction and no significant associations were found between marketing mix (place, price, promotion) and outpatient